2021
DOI: 10.11648/j.ijae.20210603.13
|View full text |Cite
|
Sign up to set email alerts
|

Profitability Analysis of Rain Fed Upland Rice Production Under Smallholder Farmers in Libokemkem District, North Western Ethiopia

Abstract: Cultivation of rice in Ethiopia is a recent phenomenon and the crop provides advantages to rice farmers in regarding productivity basis compared to other cereal crops and contribute a lot towards ensuring food security in the country. With the advantage related to the higher productivity, the ever-increasing of domestic demand as a result of urbanization and population growth, rice production under smallholder farmers is expanding very fast. The study was designed to determine the cost of production and profit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Production BEP is the minimum amount of output required to cover production costs. At the point of BEP, the farmer does not make a profit and does not incur a loss [29,30]. The formulas for both BEPs are follows: BEP-Y = Total Cost/Price of the Output BEP-P = Total Cost/Total Production 2.6.…”
Section: Economic Efficiency Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Production BEP is the minimum amount of output required to cover production costs. At the point of BEP, the farmer does not make a profit and does not incur a loss [29,30]. The formulas for both BEPs are follows: BEP-Y = Total Cost/Price of the Output BEP-P = Total Cost/Total Production 2.6.…”
Section: Economic Efficiency Assessmentmentioning
confidence: 99%
“…Each treatment gave different revenues, but all treatments gave positive profits overall, as indicated by RCR value > 1. A previous study reported that upland rice farming in the Cross River State of Nigeria obtained an RCR of 3.06, while Ebonyi State of Nigeria had an RCR value of 1.13 and Libokemkem District, North Western Ethiopia, obtained an RCR value of 1.44 [30,53,54]. The variability of the RCR values indicates the variation of yields and outputs of the upland rice cultivation in the area.…”
Section: Yield Profitability (Economic Analysis)mentioning
confidence: 99%
“…Condition when a unit farm gate price is higher than a break‐even price, the farm is in economic profit (Abera et al. 2019) and was calculated by using the formulas:leftBreakeven priceNRs/kg=Total production costNRs/ha/Total productionkg/ha,$$ {\displaystyle \begin{array}{c}\mathrm{Break}-\mathrm{even}\ \mathrm{price}\ \left(\mathrm{NRs}/\mathrm{kg}\right)=\mathrm{Total}\ \mathrm{production}\ \mathrm{cost}\ \left(\mathrm{NRs}/\mathrm{ha}\right)\hfill \\ {}\kern12em /\mathrm{Total}\ \mathrm{production}\ \left(\mathrm{kg}/\mathrm{ha}\right),\end{array}} $$leftBreakeven yieldkg/ha=Total production costNRs/ha/Selling priceNRs/kg.$$ {\displaystyle \begin{array}{c}\mathrm{Break}-\mathrm{even}\ \mathrm{yield}\ \left(\mathrm{kg}/\mathrm{ha}\right)=\mathrm{Total}\ \mathrm{production}\ \mathrm{cost}\ \left(\mathrm{NRs}/\mathrm{ha}\right)\hfill \\ {}\kern10em /\mathrm{Selling}\ \mathrm{price}\ \left(\mathrm{NRs}/\mathrm{kg}\right).\end{array}} $$…”
Section: Methodsmentioning
confidence: 99%